PERANCANGAN SISTEM PENGUNCIAN RODA SATU ARAH UNTUK MENGEMUDIKAN KENDARAAN RODA EMPAT DI JALAN MENANJAK - Helmahera, Doni; Wiharta, Dewa Made; Suartika, I Made (Jurnal SPEKTRUM, 2020)
Handbrake of a vehicle is the most important thing in a safety system in maintaining the position of the vehicle in its stop position. The hand brakes function to brake or lock the rear wheels mechanically through the connecting rods and cables. The hand brake is also to park the vehicle on a down/climb road. In order to facilitate the ability of four-wheeled vehicles when stopping on the ramp due to traffic jams, a special wheel locking system is used on the ramp. In a one-way wheel shooting system when a four-wheeled vehicle stops on the ramp, the system locks the wheel when the wheel rotates slightly backwards without having to pull the handbrake lever. Therefore, this research aims to describe how the work of the one-way wheel locking system when on the ramp of a four-wheeled vehicle. At the design of this system researchers make prototype as a simulation system that is approaching similar to the shape of components of a four-wheeled vehicle. Researchers perform test system work when the prototype moves forward and backwards to find out if the system is capable of locking the wheels when the move is backward and release the locking wheel when moving forward without using the hand brake. Using a one-way wheel locking system is expected to facilitate the driver in driving four-wheeled vehicles on the ramp without having to use the hand brake.